Perancangan E-CRM pada PT Multi Superindo Manunggal - Djojo, Brata Wibawa; Tamara, Karin (Journal the Winners: Economics, Business, Management, and Information System Journal, 2010)
The key to the success of a company does not only lie in the product or service being offered, but in how far the company's efforts in satisfying the needs of its customers. Results of the system analysis, shows that problems faced by the company are caused by still not optimal customer services. The purpose of this study is to analyze the appropriate strategy for the company and design systems to support the implementation of the strategy. The analytical method used in analyzing the industry with Porter's Five Forces model, and formulation of strategies for using the method of analysis of external and internal environment with matrix IFE and EFE, followed by a SWOT matrix, and strategy decisions based on the matrix QSPM. Results from the formulation of strategy are market penetration strategy. E-CRM system is considered to be the most appropriate in implementation of this strategy and overcoming the problems faced by the company. Web-based e-CRM systems, focusing on the development and maintenance of long-term relationships with customers that can provide added value to both. E-CRM system is expected to make transactions easier for customers to order and get customer service, and also for prospective customers to access accurate company information. Design of E-CRM systems are conducted using 7C method.